Simple Determination of Enthalpy and Entropy of Refrigerant Fluids - Nejabat, Rozita (Asian Journal of Chemistry, 2010)
The present work employs a simplified procedure for calculation of parameters in Tao-Mason (TM) equation of state to calculate thermodynamic properties of refrigerant fluids. The calculations cover the ranges from the dilute vapour or gas to highly compressed liquid and supercritical region. The thermodynamic properties are the vapour and liquid densities, the enthalpy, the entropy, etc. The theoretical equation of state (EOS) is that of Tao-Mason which is based on statistical mechanical perturbation theory. The first parameter which plays an important role in the EOS is the second virial coefficient. In the present work this parameter is calculated from a two-parameter corresponding states correlation along with two constants i.e., enthalpy of vaporization and molar density both at the normal boiling temperature. Two remained parameters in Tao-Mason EOS (i.e. α, λ and b) are obtained from simple equation. The novelty of the present work is that we use two scaling constants including enthalpy of vaporization and molar density both at the normal boiling temperature instead of using five scaling constants including critical temperature and pressure, Boyle temperature and pressure and acentric factor in calculating three parameters temperature dependent second virial coefficient, α and b. This EOS is applied to 12 ozone-friendly refrigerants. In general, the results are in very good agreement with experimental data.